STUDENTS' PERCEPTION ON THE USE OF YOUTUBE TOWARDS THEIR SPEAKING SKILL - Muhammad Andi Rusgandi (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
Nowadays, English has been spoken globally around the world. Therefore, mastering English speaking skill is very important for the students especially who study English as a Foreign Language. Because of that, the demand of the students who want to study English were getting higher over time. However, students tend to struggle in mastering English speaking skill since English was not their mother tongue. Moreover, at the moment, students studied English speaking skill online due to the pandemic of Covid-19. Therefore, regarding to the facts above, this research aimed to investigate the students’ perception on the use of YouTube as their means to learn English speaking skill. In this study, the researcher used qualitative approach with the descriptive design. The participants of this study were 30 English students of second semester of the English Education Department at UNISMA. However, there were only 10 students to be interviewed as the representatives of 30 responses. The instrument used in this study were questionnaire using likert scale and semi-structured interview. The finding showed that all of the students agreed that YouTube played a significant role in improving their speaking skill. Even though there were still a few students who faced problem related to the network constraints when they were using YouTube, yet it was not a big problem for them. In fact, by the use of YouTube the students stated that their pronunciation and fluency was getting better. Not only that, their vocabulary was also enhanced. All of the students also stated that YouTube was very flexible to use, so that the students could practice their speaking skill by using YouTube whenever and wherever they want. All in all, the students had a positive perception on the use of YouTube towards their speaking skill.